Eksplorasi Pengalaman Guru Dalam Mengimplementasikan Pembelajaran Berbasis Teknologi - Fauzan Sholeh, Rifqi (Jurnal Syntax Fusion, 2024)
This study explores teachers' experiences in implementing technology-based learning through an interpretive phenomenological approach with a constructivist paradigm. The research aims to deeply understand how teachers construct meaning and transform their pedagogical practices in the context of technology integration. The study was conducted in five senior high schools involving 12 teachers from various subject areas selected through purposive sampling. Data were collected through semi-structured in-depth interviews, participatory classroom observations, and analysis of teachers' reflective documents, then analyzed using six-phase thematic analysis. Research trustworthiness was maintained through data source triangulation, member checking, peer debriefing, and reflexive journaling. The findings identified five main themes representing the essence of teachers' experiences: (1) a journey of professional identity transformation involving fundamental reconstruction of teaching and learning, (2) negotiation of multi-layered barriers at individual, institutional, and socio-cultural levels through adaptive strategies, (3) reconstruction of pedagogical practices through reflective trial-and-error cycles, (4) complex emotional dynamics between enthusiasm and frustration affecting implementation persistence, and (5) formation of learning communities as survival strategies providing emotional support and practical knowledge. The findings indicate that technology implementation is not merely the adoption of digital tools but rather a socio-emotional-cognitive transformation process occurring within a complex ecosystem. The practical implications of this research emphasize the need for a shift in professional development policies from top-down approaches based on technical training toward bottom-up approaches responsive to teachers' actual needs, facilitating communities of practice, and providing adequate emotional support.